Exploring the Integration of Artificial Intelligence in Clinical Laboratory Diagnostics Education: Opportunities and Challenges - Xie, Chengxia; Li, Chen; Mo, Fan; Wang, Tingli (Pacific International Journal, 2025)
The rapid development of Artificial Intelligence (AI) is reshaping various sectors, particularly healthcare and education. This article explores the integration of AI in Clinical Laboratory Diagnostics Education and its potential to transform teaching and learning paradigms. AI enables personalized instruction, immersive virtual laboratories, and intelligent teaching management systems, thereby enhancing educational effectiveness and efficiency. Additionally, AI supports clinical decision-making through advanced diagnostic algorithms and multi-dimensional data analysis. Nonetheless, its implementation faces considerable challenges, including high infrastructure costs, data privacy concerns, and ethical implications. This review summarizes the current landscape, identifies critical barriers, and discusses future directions. A balanced and responsible adoption strategy is essential to maximize AI's benefits while addressing associated risks, ultimately cultivating a new generation of healthcare professionals proficient in both clinical diagnostics and AI technologies.